2019
DOI: 10.1021/acs.inorgchem.9b02745
|View full text |Cite
|
Sign up to set email alerts
|

Efficient Electrocatalytic Water Oxidation by Fe(salen)–MOF Composite: Effect of Modified Microenvironment

Abstract: An efficient and robust heterogeneous electrocatalyst, FSWZ-8 ((Fe-(salen)(OH) + H 4 [SiW 12 O 40 ]•HCl)@ZIF-8) for oxygen evolution reaction (OER) at the neutral pH, was developed by coencapsulation of Fe-salen (i.e., Fe(salen)Cl) and SiW 12 (i.e., H 4 [SiW 12 O 40 ]) inside the cavity of zeolitic imidazolate framework-8 (ZIF-8) material by an in situ synthesis. Here ZIF-8 functions as a host, Fe-salen as the active catalyst, and SiW 12 helps in the charge transport by lowering the overall electrical resista… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
39
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 50 publications
(42 citation statements)
references
References 74 publications
2
39
1
Order By: Relevance
“…In the observed overpotential, a large contribution should be present from the resistive nature of ZIF‐8. A comparison with the previously reported ZIF‐8 based electrochemical OER catalysts by our group suggests the CTMZ‐8 to possess the lowest overpotential requirement among the host‐guest composites prepared using molecular catalysts and ZIF‐8 which can perform OER in neutral pH [2,53] . This clearly depicts the outstanding performance of CTMZ‐8 as heterogeneous electrochemical OER catalyst.…”
Section: Mechanistic and Kinetic Analysissupporting
confidence: 59%
See 1 more Smart Citation
“…In the observed overpotential, a large contribution should be present from the resistive nature of ZIF‐8. A comparison with the previously reported ZIF‐8 based electrochemical OER catalysts by our group suggests the CTMZ‐8 to possess the lowest overpotential requirement among the host‐guest composites prepared using molecular catalysts and ZIF‐8 which can perform OER in neutral pH [2,53] . This clearly depicts the outstanding performance of CTMZ‐8 as heterogeneous electrochemical OER catalyst.…”
Section: Mechanistic and Kinetic Analysissupporting
confidence: 59%
“…Faradic efficiency of conversion of electrical energy to chemical energy has been calculated by determining the amount of evolved gas (Figure 8) under chronopotentiometric measurement using a home‐made setup following a protocol, we have reported earlier [53] . Bulk electrolysis using a volumetric set‐up was carried out at constant current for 8 hours using a two electrode system.…”
Section: Mechanistic and Kinetic Analysismentioning
confidence: 99%
“…The authors attributed this observation to the fact that the POM not only increased the hydrophilicity of the catalyst and facilitated the charge conduction in ZIF-8, but also ensured a higher loading of the Fe-salen complex within ZIF-8. Another way to decrease this overpotential for oxygen evolution and thus improve the hydrogen production efficiency was reported by Pang and coworkers [139]. In this work, the authors demonstrated the successful coating of ZIF-67 with a catalytically active Keggin POM, H3PW12O40.…”
Section: Electrocatalysismentioning
confidence: 76%
“…[66,67] In Bode plots of Z vs log(frequency), the straight lines in the low frequency region and high frequency region are ascribed to the impedance of the resistance and capacitance, respectively. [68] In the low-frequency region (linear portion of the curves), with increasing the frequency, the great decrease of charge-transfer resistance of CuCo 2 S 4 /CC compared to that of CoS 1.097 /CC and CuS/CC showed significantly enhanced charge transfer characteristics and catalytic performance. In addition, the potential of the CuCo 2 S 4 /CC is well kept after 20 h measurements (Figure 3f), indicating that CuCo 2 S 4 /CC is an excellent catalyst with highly stable and active for HER reaction.…”
Section: Electrochemical Hydrogen and Oxygen Evolution Performancesmentioning
confidence: 89%
“…[66,67] With the increase of the frequency In the low-frequency region, the CuCo 2 S 4 /CC shows great decreased charge-transfer resistance than CoS 1.097 /CC and CuS/CC, indicating significantly enhanced charge transfer characteristics and catalytic performance. [68] Cyclic voltammetry (CV) was used to characterize the redox behavior of CuCo 2 S 4 /CC. electrode ( Figure S11).…”
Section: Electrochemical Hydrogen and Oxygen Evolution Performancesmentioning
confidence: 99%